1999
DOI: 10.1128/mcb.19.3.1910
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Tetramerization in Promoter Recruitment by Stat5

Abstract: Stat5a and Stat5b are rapidly activated by a wide range of cytokines and growth factors, including interleukin-2 (IL-2). We have previously shown that these signal transducers and activators of transcription (STAT proteins) are key regulatory proteins that bind to two tandem gamma interferon-activated site (GAS) motifs within an IL-2 response element (positive regulatory region III [PRRIII]) in the human IL-2R␣ promoter. In this study, we demonstrate cooperative binding of Stat5 to PRRIII and explore the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
2
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(187 citation statements)
references
References 38 publications
4
178
2
3
Order By: Relevance
“…To characterize the composition of the IL-2-inducible complexes, EMSAs were performed with three probes corresponding to human GASd/EBSd, FcgRI GAS and mouse site I (Table 1). In contrast to previous reports (John et al, 1999;Meyer et al, 1997), the three probes revealed both complexes in human T cell nuclear extracts, evidencing that they were not a singularity of the human GASd/EBSd element ( Figure 1b). Supershift and inhibition of binding assays were performed with speci®c antisera.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…To characterize the composition of the IL-2-inducible complexes, EMSAs were performed with three probes corresponding to human GASd/EBSd, FcgRI GAS and mouse site I (Table 1). In contrast to previous reports (John et al, 1999;Meyer et al, 1997), the three probes revealed both complexes in human T cell nuclear extracts, evidencing that they were not a singularity of the human GASd/EBSd element ( Figure 1b). Supershift and inhibition of binding assays were performed with speci®c antisera.…”
Section: Resultscontrasting
confidence: 99%
“…This argues against an IL-2 inducible cooperative binding on both sites but does not preclude their functional interaction. Moreover, we con®rmed our previous report (Lecine et al, 1996) and observed e cient binding of two GAS-speci®c complexes on monomeric GAS-speci®c motif using both tumoral and primary human T cell extracts, whereas John and collaborators (John et al, 1999) did not report any signi®cant Stat5 binding with a monomeric GASc probe (almost identical of our GASd/EBSd probe). We did not elucidate this discrepancy but we suspect some di erences in EMSA protocols.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The N-terminal domain is involved in STAT dimerization and also in tertramerization interactions. The tetramerization of STATs contributes to stability of the STAT-DNA binding by means of the interaction with randomly arranged low-affinity STAT binding sites, thus increasing transcriptional activity [83]. Several studies have implicated the N-domain in various protein-protein interactions affecting transcription and it has been suggested that this domain enables dimerized STAT molecules to polymerize and to bind multiple DNA sites that are involved in oncogenic growth signaling pathways [84].…”
Section: Structure Of Stat Proteinsmentioning
confidence: 99%